Divine-Human Intersubjectivity and the Problem of Evil - Bracken, Joseph A. (Open theology, 2018)
The use of the interrelated terms divine primary causality and creaturely secondary causality to describe the God-world relationship presents problems to Christian philosophers and theologians in dealing with two key issues: first, the freedom of human beings (and to some extent other finite entities) to exercise their own causal powers in independence of Divine Providence for the world of creation; secondly, the responsibility of God and all creatures for the existence of natural evil and the corresponding responsibility of God and human beings for the existence of moral evil in this world. After reviewing some of the ways these issues have been dealt with in the past, the author offers his own solution in terms of a Neo-Whiteheadian systems-oriented approach to the God-world relationship with emphasis on a reciprocal causal relationship between God and creatures so as conjointly to bring about everything that happens in this world.